Pulse wave analysis and diabetes mellitus. A systematic review - Gajdova, Jaromira; Karasek, David; Goldmannova, Dominika; Krystynik, Ondrej; Schovanek, Jan; Vaverkova, Helena; Zadrazil, Josef (Biomedical papers, 2017)
Cardiovascular (CV) disease is the primary cause of death in diabetic patients and one of the explanations may be increased arterial stiffness. Arterial stiffness assessment using pulse wave analysis, is a predictive factor of CV events. The aim of this paper is to review the current knowledge of relations between diabetes mellitus and pulse wave analysis. A MEDLINE search was performed to retrieve both original and review articles addressing the relations and influences on arterial stiffness in diabetics. Pulse wave analysis is considered as a gold standard in CV risk evaluation for patients at risk, especially diabetics. Arterial stiffness assessment may be helpful for choosing more aggressive diagnostic and therapeutic strategies, particularly in younger patients to reduce the incidence of CV disease in these patients.
Keywords: diabetes mellitus; arterial stiffness; pulse wave analysis